Oralność i retoryka świętych ksiąg. Na przykładzie tatarskiego tefsiru – pierwszego przekładu Koranu na język słowiański ( polski ) - Kulwicka-Kamińska, Joanna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
The article presents, on the basis of a sixteenth-century translation of the Qur’an into Polish, the interpenetration of two planes in revealed books: the rhetorical and the persuasive one. In this context, the article points out the realisation of the directives of classical Arabic rhetoric, including the semantic principle, the principle of clear expression and the principle of sophisticated style. It also indicates the original orality of the Qur’an and the persuasiveness of its message achieved, among other things, by addressing the recipient, the establishment of the us vs. them opposition, the occurrence of evaluative and directive vocabulary, the introduction of colloquial speech, and the use of intensifiers of content. The collected material also demonstrates the complex relation between the scripturalisation of a language and the translation of a sacred text ( the Qur’an ) into Polish.